PENGARUH KESESUAIAN KOMPENSASI, PENERAPAN SISTEM INFORMASI AKUNTANSI DAN EFEKTIVITAS PENGENDALIAN INTERNAL TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI - Animah SE; Widia Astuti; Handri Amin Effendi (Jurusan Akuntansi Fakultas Ekonomi Dan Bisnis Universitas Mataram, 2018)
This research is conducted to find out the test result of influence of compensation compatibility, application of accounting information system and effectiveness of internal control to tendency of accounting fraud on travel in mataram city. The population in this study as many as 194 employees and the sample used as many as 122 employees are determined by using purposive sampling method. Hypothesis testing method used is multiple linear regression analysis. The result shows that the application of accounting information system has a positive effect on the tendency of accounting fraud. While the comensation compatibility and effectiveness of the internal control does not positively affect the tendency of accounting fraud.